2019
DOI: 10.2147/cmar.s210979
|View full text |Cite
|
Sign up to set email alerts
|

<p>The role of digital breast tomosynthesis in breast cancer screening: a manufacturer- and metrics-specific analysis</p>

Abstract: Aim: Digital Breast Tomosynthesis (DBT), with or without Digital Mammography (DM) or Synthetic Mammography (SM), has been introduced or is under consideration for its introduction in breast cancer screening in several countries, as it has been shown that it has advantages over DM. Despite this there is no agreement on how to implement DBT in screening, and in many cases there is a lack of official guidance on the optimum usage of each commercially available system. The aim of this review is to carry out a manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…For smaller masses, DM may present an advantage as seen in the case of micro-calcification detection t asks. 9 This longitudinal trial is the first in silico longitudinal trial reported that evaluates the performance of imaging modalities such as DM and DBT throughout the early stages of mass lesions. In the future, we plan to include larger variability in the trial population, a more sophisticated tumor growth model as well as in silico replicas of other commercially available DM/DBT systems.…”
Section: Discussionmentioning
confidence: 99%
“…For smaller masses, DM may present an advantage as seen in the case of micro-calcification detection t asks. 9 This longitudinal trial is the first in silico longitudinal trial reported that evaluates the performance of imaging modalities such as DM and DBT throughout the early stages of mass lesions. In the future, we plan to include larger variability in the trial population, a more sophisticated tumor growth model as well as in silico replicas of other commercially available DM/DBT systems.…”
Section: Discussionmentioning
confidence: 99%
“…As more extensively presented in Hadjipanteli et al 2019 [ 31 ], the combination of 1vDBT or 2vDBT with 1vDM or 2vDM was investigated in several studies [ 1 , 2 , 4 , 43 46 ], with the difference that its implementation was in breast cancer screening and not surveillance imaging. Rafferty et al [ 4 ] showed that using Hologic 2vDM, 2vDM&1vDBT, and 2vDM&2vDBT the AUCs were 0.828, 0.864, and 0.895 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…One solution to the increased patient dose, image interpretation time and storage capacity could potentially be the replacement of DM by SM [ 29 , 30 ] as it has been shown that SM is at least non inferior to DM. As more extensivity discussed in Hadjipanteli et al [ 31 ] several studies, carried out after Hologic SM was approved by FDA, support that the performance of SM is least equal in terms of sensitivity (43,44), specificity (44,45), AUC (97), cancer detection rate (97) and recall rate (100–103) However, work is still undertaken on the optimal utilization of SM [ 32 ] and there is therefore uncertainty on its use in screening. Furthermore, not all hospitals and breast imaging centres have the immediate financial capacity to get access to SM, as it requires at least a specialised image analysis software, which forms an additional separate cost to tomosynthesis and cannot always be easily justified.…”
Section: Introductionmentioning
confidence: 99%
“…The longer reading time, together with the limited availability of equipment and higher total cost for DBT, are all barriers for a wider implementation 10 , 11 . Also, the organ dose is often higher with DBT, 12 though this may depend on equipment and way of implementation.…”
Section: Introductionmentioning
confidence: 99%